Analisis Pemasaran Interaktive Dalam Menarik Minat Konsumen Berbelanja Online Dan Kepuasan Berbelanja - Nurdiana; Pristiyono; Mulkan Ritonga (Journal of Trends Economics and Accounting Research, 2023)
This study aims to find out: (1) the effect of interactive marketing on online shopping satisfaction in Panai Hilir sub-district, (2) the effect of interactive marketing on consumer interest in online shopping in Panai Hilir sub-district, and (3) the effect of interactive marketing on shopping satisfaction in Panai Hilir sub-district mediated by consumer interest. This research is qualitative research. The sampling technique used in this study was purposive sampling. Data collection techniques use questionnaires that have been tested for validity and reliability. The data analysis techniques used to answer this research hypothesis are path analysis and sobel tests. The results of the study at the 5% significance level showed that: (1) there is an influence of interactive marketing strategies on shopping satisfaction. (2) there is an influence of shopping interest on shopping satisfaction